2020
DOI: 10.1097/dbp.0000000000000865
|View full text |Cite
|
Sign up to set email alerts
|

Growing Up Fast: Managing Autism Spectrum Disorder and Precocious Puberty

Abstract: CASE: John is a 4-year-old boy with autism spectrum disorder (ASD) and developmental delay who presented with concerns about increasing aggressive behavior at a follow-up visit with his developmental-behavioral pediatrician. Diagnosis of ASD was made via Diagnostic and Statistical Manual of Mental Disorders, 5th version criteria at initial evaluation at 34 months. Medical history at that time was pertinent for rapid linear growth since the age of 1 and recent pubic hair growth and penile enlargemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Other studies identified from a literature review included case reports of PP occurring in children diagnosed with an ASD [21,22] and other investigators reporting on a case series of children diagnosed with an ASD and PP [23]. These studies concluded, consistent with the known association between PP and other childhood central nervous system disorders, children diagnosed with an ASD are at an increased risk for being diagnosed with PP.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies identified from a literature review included case reports of PP occurring in children diagnosed with an ASD [21,22] and other investigators reporting on a case series of children diagnosed with an ASD and PP [23]. These studies concluded, consistent with the known association between PP and other childhood central nervous system disorders, children diagnosed with an ASD are at an increased risk for being diagnosed with PP.…”
Section: Discussionmentioning
confidence: 96%
“…In recent years, some reports of CPP have been reported in children with ASD [4][5][6][7]. David and Mark [7] reported that the precocious puberty rate was 3.15 times higher in the ASD group than in the control group and that precocious puberty was more likely to occur after three years of age.…”
Section: Case Presentationmentioning
confidence: 99%
“…The contribution of genetic factors to precocious puberty has been previously reported [ 1 - 3 ]. Of these, an association between autism spectrum disorder (ASD) and central precocious puberty (CPP) has been suggested [ 4 - 7 ]. Herein, we describe two cases of CPP associated with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…ASD comorbid with specific neuropsychiatric disorders may suggest a unique pathophysiology that differs from ASD alone [16,17]. In our review, sporadic case reports documented precocious puberty in patients with ASD [18,19]. However, large-scale studies on the association between these two medical conditions remain scarce.…”
Section: Introductionmentioning
confidence: 91%